Association of valproate use and hippocampal atrophy in idiopathic generalized epilepsy - Xiang Huang; Yingying Zhang; Qiuxing Lin; Kailing Huang; Yuming Li; Peiwen Liu; Danyang Cao; Wenhao Li; Wei Li; Xiuli Li; Qiyong Gong; Dong Zhou; et al. (NeuroImage: Clinical)
Objective: Recent studies revealed the effect of valproate (VPA) on brain structural changes in idiopathic generalized epilepsy (IGE). We aimed to investigate the volume of the entire hippocampus and subfields in patients with IGE, and explored their associations with VPA use. Methods: A total of 211 patients with IGE and 97 healthy controls (HCs) were enrolled in this study. All participants underwent T1-weighted images. Each hippocampus was segmented into seven subfields using HippUnfold. The volumes of bilateral hippocampi and each hippocampal subfield were evaluated. Spearman correlation analyses were performed to identify VPA use related abnormalities in IGE. Subgroup analyses for juvenile myoclonic epilepsy (JME), epilepsy with generalized tonic–clonic seizures alone (GTCA), and absence epilepsy (AE) were conducted. Results: The volumes of bilateral hippocampi were reduced in IGE compared with HCs. Subgroup analysis showed significant volume reductions in right hippocampus and its subfields in GTCA. Additionally, significant volume reductions were detected in bilateral hippocampal volumes and subfields in IGE patients currently taking VPA compared with HCs. A negative correlation was observed between the left CA2 volume and the age of onset. Conclusions: Our study revealed volume reductions in bilateral hippocampi in IGE, as well as in the right hippocampus and its subfields in GTCA. Abnormalities in both subfields and the whole hippocampus were associated with VPA use. These findings suggest that VPA may have more extensive neuroanatomical effects in IGE, potentially accounting for the heterogeneity observed in neuroimaging studies.